Scavenger receptors: diverse activities and promiscuous binding of polyanionic ligands - Platt, N; Gordon, S (Elsevier, 1998)
Scavenger receptors are a diverse family of proteins that share a common property – the binding of modified lipoprotein – but they have recently been shown to recognise a diverse range of ligands. Understanding the molecular interaction of receptor-ligand binding should provide insight into how scavenger receptors contribute to important biological processes.